Management of the Conducted Noise Circulation in X-IFU Instrument - Maisonnave, Oceane; Gloaguen, Emilie; Van Leeuwen, Bert-Joost; Peille, Philippe; Geoffray, Herve (2025 ESA Workshop on Aerospace EMC (Aerospace EMC), 2025)
This paper describes the simulation strategy implemented to assess the impact of the common monde noise circulation in an environment highly constrained by performance expectations and thermal architecture. The modeling of the resistive cryoharness used in the X-IFU (=X-ray Integral Field Unit) instrument is described and characterised by test. A correlation with simulations allows validating the harness model to be implemented in the EMC simulator of the detection chain.